Analysis of the Effectiveness of Government Policy in Poverty Reduction Program in Madiun District: Analisis Efektivitas Kebijakan Pemerintah dalam Program Pengentasan Kemiskinan di Kabupaten Madiun - Wardani, Alvionita Rizky; Arif, Muhammad (Procedia of Social Sciences and Humanities, 2022)
This study aims to analyze the effectiveness of government policies in poverty alleviation programs in Madiun Regency. this research uses panel data method using eviews8 software. From the results of the study, it can be concluded that partially the Smart Indonesia Program and Non-Cash Food Assistance variables have a negative but significant effect on poverty, while the Village Fund has a positive and significant effect on poverty and the Family Hope Program has a negative effect on poverty. While the simultaneous influence of the Village Fund variable, Family Hope Program, Non-Cash Food Aid, Smart Indonesia Program is significant at 63.74% and the remaining 36.26% is influenced by other factors that are not included in the model. This research is expected to be a consideration for the government in poverty alleviation programs in Madiun Regency in order to reduce poverty in the area.